Kontekstualitas Islam Tentang Identitas Gender Waria - Nur Kholis (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
This article aims to find out the answer of gender identity polemic of transsexual in Islamic thought. Therefore, tracking the foundation of Islamic thought in the Qur’an about transsexual’s gender identification is required due to the fact that someone’s Islamic attitude is always determined by one’s interpretation. The results found indicated that the Islamic contextuality of transsexual’s gender identity can be propped on QV. Al-Hajj [22]: 5 and QV. Al-Nur [24]: 31. From those two verses, it is understood that: (1) The transsexual phenomenon is “natural reality” as imperfect created beings since in the form of a fetus (mudlghah ghairi mukhallaqah); (2) The transsexual are exception for women to cover her aurat, because of the condition as men who do not have sexual desire on women (ghairi uli al-irbat min al-rijal). This conclusion is validated from the meaning of the hadith of the Prophet who cursed transvestites as intentional behavior (bi al-qashdi/ bi takalluf), not because of the nature that cannot be avoided (bi al-khalq/ min ashl al-khilqat). In the circumstances of this kind mukhannats khalqi, the existance of transsexual’s gender identity is not cursed and even received in Islam.[Artikel ini hendak menemukan jawaban atas polemik identitas gender waria dalam pemikiran keislaman. Untuk itu, pelacakan landasan pemikiran keislaman dalam al-Qur’an tentang identifikasi gender waria diperlukan mengingat sikap keislaman seseorang senantiasa ditentukan oleh cara “bertafsir”nya. Hasil yang ditemukan menunjukkan bahwa kontekstualitas Islam mengenai identitas gender waria dapat disandarkan pada QS. Al-Hajj [22]: 5 dan QS. Al-Nur [24]: 31. Dari kedua ayat ini dapat dipahami bahwa: (1) fenomena waria merupakan “kenyataan kodrati” sebagai makhluk yang tercipta tidak sempurna sejak dalam bentuk janin (mudlghah ghairi mukhallaqah); (2) karena kondisinya sebagai laki-laki yang tidak berhasrat secara seksual terhadap perempuan (ghairi uli al-irbat min al-rijal), waria menjadi pengecualian bagi perempuan untuk menutup auratnya. Kesimpulan ini dikuatkan dari pemaknaan atas hadits Nabi yang melaknat waria karena perilakunya yang disengaja (bi al-qashdi/ bi takalluf), bukan karena kodrat yang tidak mungkin dihindarinya (bi al-khalq/ min ashl al-khilqat). Dalam keadaan mukhannats khalqi semacam ini, kenyataan identitas gender waria tidak dilaknat dan bahkan diterima keberadaannya dalam Islam.]